Pemetaan Daya Dukung Lingkungan Lahan Basah Desa Tanjung Buka Dalam Penyediaan Air dan Pangan - Adi Sutrisno (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
Changes in land cover caused by development activities carried out by humans have occurred a lot in Indonesia. It can cause a decrease in the carrying capacity of the environment. Therefore, this study aimed to assess the status of the environmental carrying capacity of the Tanjung Buka Village wetland, geographically located at 117°21'0